Konsep Ta’lim wa Ta’dib dalam pemikiran KH. Hasyim Asy’ari di Majelis Hidayatul Mubtadiin - Habibudin, Fuad; Maulana, M. Fahmi; A'yunin, Siti Khurota (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the relevance of KH Hasyim Asy’ari’s educational concept—which integrates ta’lim (religious instruction) and ta’dib (moral guidance)—in the practice of religious education at the Majelis Hidayatul Mubtadiin (HM) in Tulakan, Pacitan. This study employs a qualitative approach using the case study method. Data collection was conducted through in-depth interviews with the majelis’s leaders, accompanied by observations of learning activities and the moral guidance of the students. The results indicate that KH Hasyim Asy’ari’s educational concept remains highly relevant and is concretely applied at the HM Majelis. This implementation is evident in the teaching of classical Islamic texts, tafsir (Qur’anic exegesis) studies, and moral character development through mujahadah (spiritual discipline) activities, the strengthening of the bond of mutual affection (muhabat) between teachers and students, and the cultivation of the habit of reciting shalawat (prayers of blessings upon the Prophet). This integration of ta’lim and ta’dib not only deepens the students’ religious understanding but also shapes a character and moral conduct that is moderate, adaptive, and responsive to contemporary challenges, such as radicalism and the influence of social media. This approach is considered effective in maintaining a balance between the mastery of knowledge and moral development. Abstrak Penelitian ini bertujuan untuk menganalisis relevansi konsep pendidikan KH Hasyim Asy’ari yang mengintegrasikan ta’lim (pengajaran ilmu agama) dan ta’dib (pembinaan akhlak) dalam praktik pembelajaran keagamaan di Majelis Hidayatul Mubtadiin (HM) Tulakan, Pacitan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan melalui wawancara mendalam dengan pengasuh majelis, disertai observasi terhadap aktivitas pembelajaran dan pembinaan santri. Hasil penelitian menunjukkan bahwa konsep pendidikan KH Hasyim Asy’ari masih sangat relevan dan diterapkan secara konkret di Majelis HM. Implementasi tersebut tampak dalam pengajaran kitab kuning, kajian tafsir, serta pembinaan akhlak melalui kegiatan mujahadah, penguatan hubungan muhabat antara guru dan murid, dan pembiasaan pembacaan shalawat. Integrasi ta’lim dan ta’dib ini tidak hanya meningkatkan pemahaman keagamaan santri secara mendalam, tetapi juga membentuk karakter dan akhlak yang moderat, adaptif, serta responsif terhadap tantangan kontemporer, seperti radikalisme dan pengaruh media sosial. Pendekatan ini dinilai efektif dalam menjaga keseimbangan antara penguasaan ilmu dan pembentukan moral.